2013
DOI: 10.1530/joe-13-0010
|View full text |Cite
|
Sign up to set email alerts
|

2D-DIGE to identify proteins associated with gestational diabetes in omental adipose tissue

Abstract: Gestational diabetes mellitus (GDM) is a significant risk factor for the type 2 diabetes epidemic in many populations. Maternal adipose tissue plays a central role in the pathophysiology of GDM. Thus, the aim of this study was to determine the effect of GDM on the proteome of adipose tissue. Omental adipose tissue was obtained at the time of term Caesarean section from women with normal glucose tolerance (NGT) or GDM. 2D-difference gel electrophoresis (DIGE), followed by mass spectrometry, was used to identify… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

2
37
1
1

Year Published

2014
2014
2022
2022

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 45 publications
(43 citation statements)
references
References 58 publications
(61 reference statements)
2
37
1
1
Order By: Relevance
“…In addition, NOD1 activation provokes adipose tissue inflammation in vivo (Schertzer et al 2011). Collectively, these results indicate that NOD1 activation may facilitate the infiltration of leukocytes into adipose tissue, leading to adipose inflammation, a key feature of GDM pregnancies (Lappas 2013a, Oliva et al 2013. Moreover, NOD1-mediated release of pro-inflammatory cytokines from adipose tissue may directly contribute to the insulin resistance that is evident in pregnancies complicated by GDM (Catalano et al 2002, Colomiere et al 2010.…”
Section: Figurementioning
confidence: 96%
See 1 more Smart Citation
“…In addition, NOD1 activation provokes adipose tissue inflammation in vivo (Schertzer et al 2011). Collectively, these results indicate that NOD1 activation may facilitate the infiltration of leukocytes into adipose tissue, leading to adipose inflammation, a key feature of GDM pregnancies (Lappas 2013a, Oliva et al 2013. Moreover, NOD1-mediated release of pro-inflammatory cytokines from adipose tissue may directly contribute to the insulin resistance that is evident in pregnancies complicated by GDM (Catalano et al 2002, Colomiere et al 2010.…”
Section: Figurementioning
confidence: 96%
“…There is now some evidence that metabolic endotoxemia originating from the diet or the environment disrupts the balance between the immune and the metabolic systems (Cani et al 2007) which may lead to GDM. Thus, it is possible that this increase in bacteria may activate NOD1, leading to the increased inflammation and insulin resistance observed in women with GDM (Garvey et al 1993, Colomiere et al 2010, Lappas 2013a, Oliva et al 2013. Indeed, it has recently been shown that dietinduced modification of the gut flora with probiotics can ameliorate the insulin resistance and glucose homoeostasis of pregnant women (Laitinen et al 2009).…”
Section: Figurementioning
confidence: 99%
“…Up to now, no comprehensive proteomic analyses of plasma related to GDM have been reported. Only a few proteomic analyses of placental, omental adipose tissue related to GDM have been reported [9,10]. However, comprehensive analysis of the plasma is a challenging task because of its extraordinary complexity and high dynamic range in concentration [11].…”
Section: Introductionmentioning
confidence: 99%
“…Several studies have reported abnormal expression of different proteins involved in glucose and lipid metabolism [23], inflammation [24] and oxidative stress [25] in GDM and thus, intricate…”
Section: Introductionmentioning
confidence: 99%